Sustainability Analysis of the Chemical Industry in the Period of Transformation Using an Institutional Approach - V. G. Kogdenko; N. A. Kazakova (Финансы: теория и практика)
The relevance of the study is related to the need to monitor the sustainability of business and improve the institutions of its regulation during the period of transformation of the national economic model focused on technological sovereignty. In this regard, the purpose of the study was to develop a methodology for analyzing the sustainability of business models of behavior of companies in the chemical industry using an institutional approach to assess the influence of institutional aspects on the performance of companies belonging to different institutional groups, as well as assessing the transformation in general. The scientific novelty of the study lies in the development of analytical tools for assessing the behavior of companies of various institutional groups, which allows us to identify ongoing trends and acts as a navigator for the structural transformation of the industry. According to the results of the study, the most significant institutional factors of the efficiency and sustainability of business behavior models that influence the effectiveness of transformation are participation in government procurement and the mandatory external audit. The author’s approach to the formation of institutional groups of companies based on criteria for assessing their business behavior model from the perspective of operational efficiency, investment activity, and financial stability is of theoretical significance. The practical value lies in the development of an algorithm for identifying points of promising economic growth and indicators for assessing industry transformation to provide support to companies with the greatest multiplier effect. The results obtained can be used in the implementation of priority projects of technological sovereignty and projects of structural adaptation of the economy, as well as the concept of technological development of the Russian Federation for the period until 2030, as a tool for monitoring their implementation and determining the vector of development of priority sectors of the economy, searching for new potential points of economic growth, attracting public and private investments. The proposed tools may be in demand for selecting effective participating organizations in the system of public procurement and government support for business.